EFFECT OF ASHWAGANDHA ON PHARMACOKINETIC AND PHARMACODYNAMIC PARAMETERS OF GLIMEPIRIDE IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - B, Nagaraj; C, Veeresham (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present investigation is aimed to determine the effect of ashwagandha (AG) on pharmacokinetic (PK) and pharmacodynamic (PD) parameters of glimepiride (GP) in diabetic rats. Simultaneously, the effect was also studied in normal rats. Methods: Diabetes in rats was induced by streptozotocin. The PK parameters are calculated in normal and diabetic rats. PD studies were performed in diabetic rats only. Results: From the PK results, 2.26-folds of improvement in the oral bioavailability of GP in normal rats were observed when treated with GP in a combination of AG and which is statistically significant (p<0.001). In case of diabetic rats, the oral bioavailability (3.42-folds) of GP was significantly increased when coadministered with AG and was higher (about 33.5%) than the normal rats. Further, the rate of clearance and also the volume of distribution significantly changed in diabetic rats. The blood glucose levels were significantly reduced in GP and AG treated (6.15% reduction) compared to GP alone (5.45% reduction) treated diabetic rats during a period of 24 h were noticed from PD studies. The maximum reduction was observed at 6 h (55.46%) when compared with standard GP treatment (46.06%) in case of GP and AG combination treatment. Conclusion: Therefore, the results suggestive that, the AG might be advantageous as an adjuvant to GP in an appropriate quantity, and also the dose of GP may need to be adjusted to avoid any complications.